(13x+9)=(5x+9)

Simple and best practice solution for (13x+9)=(5x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (13x+9)=(5x+9) equation:


Simplifying
(13x + 9) = (5x + 9)

Reorder the terms:
(9 + 13x) = (5x + 9)

Remove parenthesis around (9 + 13x)
9 + 13x = (5x + 9)

Reorder the terms:
9 + 13x = (9 + 5x)

Remove parenthesis around (9 + 5x)
9 + 13x = 9 + 5x

Add '-9' to each side of the equation.
9 + -9 + 13x = 9 + -9 + 5x

Combine like terms: 9 + -9 = 0
0 + 13x = 9 + -9 + 5x
13x = 9 + -9 + 5x

Combine like terms: 9 + -9 = 0
13x = 0 + 5x
13x = 5x

Solving
13x = 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
13x + -5x = 5x + -5x

Combine like terms: 13x + -5x = 8x
8x = 5x + -5x

Combine like terms: 5x + -5x = 0
8x = 0

Divide each side by '8'.
x = 0

Simplifying
x = 0

See similar equations:

| -6x-5=-9 | | (5x+5)=(115) | | x-6.0=26.0 | | 7y+9=8y+1 | | 2x^4-5x=2 | | 5x+29.0=54.0 | | 2y-71.0=25.0 | | 1/3x^3-4x-11/3 | | 4w+5=3w+9 | | loge(42)=2x+1 | | 6y=-2-x | | (x*40)+(1.5x*5)=576 | | 69*200000/X=17.92 | | 5/7m35 | | -8(s+2)=28 | | x*40+1.5*x*5=30000 | | 9w=10w-4 | | 2y-63.0=10.0 | | 2b-7/3=3/3 | | x-2.0=27.0 | | -8x+6-12=-30 | | 6x+21=x+7 | | 12+4x-x=x+28 | | 5x+28.0=58.0 | | 2b-31/3=11/3 | | (x+5)=(3x-2) | | 11/30x360 | | 7x^2+8xy+y^2=45 | | (5v-9)(8-v)=0 | | ((12v^6)-(14v^3))/(2v^3) | | 2mx^2+3mx=0 | | 2(4x-3)=58 |

Equations solver categories